Transcriptome Analysis of the Harmful Dinoflagellate Heterocapsa bohaiensis Under Varied Nutrient Stress Conditions - Peng Peng; Fangxin Han; Xue Gong; Xiangyuan Guo; Ying Su; Yiwen Zhang; Jingjing Zhan (Microorganisms)
The increasing prevalence of harmful algal blooms (HABs) driven by eutrophication, particularly in China’s nearshore waters, is a growing concern. Dinoflagellate Heterocapsa bohaiensis blooms have caused significant ecological and economic damage, as well as mass mortality, in cultivated species. Nutrients are one of the primary inducers of H. bohaiensis blooms. However, the transcriptomic studies of H. bohaiensis remain sparse, and its metabolic pathways are unknown. This study analyzed the transcriptome of H. bohaiensis under varying nutrient conditions (nitrogen at 128, 512, and 880 μM; phosphate at 8, 6, and 32 μM), focusing on differential gene expression. The results indicated that deviations in nutrient conditions (higher or lower N:P ratios) led to a higher number of differentially expressed genes compared to the control (N:P ratios = 27.5), thereby underscoring their pivotal role in growth. Gene Ontology (GO) enrichment analyses showed that nutrient limitation upregulated the biosynthesis and catabolism processes while downregulating the cell cycle and division functions. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that, under nitrogen limitation, the proteasome pathways were upregulated, while photosynthesis and carbon fixation were downregulated; under phosphorus limitation, the proteasome pathways were upregulated and nitrogen metabolism was downregulated. These findings suggest that H. bohaiensis adapts to nutrient stress by adjusting its metabolic processes.